5-Bromo-2-hydroxy-4-methyl-benzaldehyde inhibited LPS-induced production of pro-inflammatory mediators through the inactivation of ERK, p38, and NF-κB pathways in RAW 264.7 macrophages. (25th October 2016) - Kim, Kil-Nam; Ko, Seok-Chun; Ye, Bo-Ram; Kim, Min-Sun; Kim, Junseong; Ko, Eun-Yi; Cho, Su-Hyeon; Kim, Daekyung; Heo, Soo-Jin; Jung, Won-Kyo
Abstract: The aim of the present study was to investigate the effects of 5-bromo-2-hydroxy-4-methyl-benzaldehyde (BHMB) on inflammatory responses to lipopolysaccharide (LPS) in RAW 264.7 cells and the associated mechanism of action. BHMB concentration-dependently suppressed protein and mRNA expressions of iNOS and COX-2, thereby inhibiting the production of NO and PGE2 in LPS-stimulated RAW 264.7 cells. BHMB also reduced the mRNA expression of TNF-α, IL-6, and IL-1β in LPS-stimulated RAW 264.7 cells. To elucidate the mechanism underlying the anti-inflammatory activity of BHMB, we investigated the effects of BHMB on the mitogen-activated protein kinase and nuclear factor-kappa B (NF-κB) pathways. BHMB suppressed the phosphorylation and degradation of IκB-α and markedly inhibited the nuclear translocation of p65 and p50 in LPS-stimulated RAW 264.7 cells. The compound also inhibited the LPS-stimulated phosphorylation of ERK and p38. Taken together, these results illustrated that BHMB suppresses pro-inflammatory mediator and cytokine expression in LPS-stimulated RAW 264.7 cells by inhibiting the phosphorylation of ERK and p38 and the activation of NF-κB. Graphical abstract: Highlights: BHMB inhibited inflammatory mediators in LPS-stimulated RAW 264.7 cells to mimic the inflammation conditions. Moreover, BHMB inhibited the LPS-induced phosphorylation of ERK, p38, and NF-κB. BHMB may have a beneficial effect on treatment of inflammatory diseases.